Using microbes to suppress overwintering inoculum of Monilinia laxa on mummified fruits and to protect cherry blossoms and fruit from infection - Bellamy, Sophia; Shaw, Michael; Xu, Xiangming (Frontiers in Horticulture, 2024)
Cherry brown rot, primarily caused by Monilinia laxa, poses a significant threat to cherry production in the UK. Traditional control methods are labour-intensive or environmentally damaging, favouring alternative solutions such as using biological control agents (BCAs). This study investigated the survival and efficacy of two BCAs, Bacillus subtilis (B91) and Aureobasidium pullulans (Y126), in reducing M. laxa populations on mummified fruits and cherry blossoms. Field experiments were conducted to assess the survival of B91 and Y126 on mummified fruits over winter and their effect on M. laxa sporulation in spring. Additionally, the efficacy of the two BCAs when applied to cherry blossoms was evaluated, at different times of application relative to M. laxa inoculation. Y126 could persist on blossoms and throughout the growing season. B91 population level declined rapidly on blossoms but recovered once fruits appeared. Neither BCA usefully reduced the concentration of M. laxa. Y126 was marginally more effective at long-term reduction. On mummified fruits, Y126 population size declined rapidly within the first two weeks after inoculation before stabilising. B91 survived slightly longer. Longer interaction times between M. laxa and the BCAs in the late winter resulted in lower spore counts of M. laxa from mummified fruits. While both BCAs reduced M. laxa populations when applied close to M. laxa inoculation, BCA populations were not maintained at effective levels throughout the growing season. These results suggest that multiple applications targeting critical periods (blossom and pre-harvest) are necessary for effective control of M. laxa by either of these BCAs.